Night of the white buffalo [large type] - Coel, Margaret, 1937- (Coel, Margaret, 1937- Wind River mystery, 2015)
"With her gritty mysteries steeped in authentic Native American culture, New York Times bestselling author Margaret Coel is "widely considered the most accomplished heir to Tony Hillerman's legacy," (Scripps Howard News Service). In the latest Wind River novel, Arapaho attorney Vicky Holden and Father John O'Malley confront a ruthless killer in the wake of a miraculous event. A mysterious penitent confesses to murder, and then flees the confessional before Father John can identify him. Two months later, Vicky discovers rancher Dennis Carey shot dead in his truck along Blue Sky Highway. With the tragic news comes the exposure of an astonishing secret: the most sacred creature in Native American mythology, a white buffalo calf, was recently born on Carey's ranch. Making national headlines, the miraculous animal draws a flood of pilgrims to the reservation, frustrating an already difficult investigation. As visitors throw the reservation into turmoil, Vicky and Father John try to unravel the strange events surrounding both Carey's murder and the recent disappearances of three cowboys from his ranch. It could be coincidence, given the nomadic life of the cowboy trade, but when one of them fails to appear in court to testify on an assault charge, Vicky wonders if Arnie Walkfast and his Arapaho buddies are guilty of more than just assault. And at the back of Father John's mind is the voice from the man in the confessional: I killed a man . . . " --